2018
DOI: 10.3390/molecules24010002
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Effect of Essential Oil Extracted from Eugenia dysenterica DC (Myrtaceae) Leaves

Abstract: The use of natural oils in topical pharmaceutical preparations has usually presented safe agents for the improvement of human health. Based on research into the immense potential of wound management and healing, we aimed to validate the use of topical natural products by studying the ability of the essential oil of Eugenia dysenterica DC leaves (oEd) to stimulate in vitro skin cell migration. Skin cytotoxicity was evaluated using a fibroblast cell line (L929) by MTT assay. The oil chemical profile was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Wound healing occurs as a cellular response to injury and during the early phase of wound repair macrophages that play a central role in tissue damage are involved in the maintenance of tissue hemostasis and initiation of inflammatory events. These cells can produce several inflammatory mediators, among them, nitric oxide (NO) is crucial for the development of subsequent events, especially the resolution of inflammation [61].…”
Section: Resultsmentioning
confidence: 99%
“…Wound healing occurs as a cellular response to injury and during the early phase of wound repair macrophages that play a central role in tissue damage are involved in the maintenance of tissue hemostasis and initiation of inflammatory events. These cells can produce several inflammatory mediators, among them, nitric oxide (NO) is crucial for the development of subsequent events, especially the resolution of inflammation [61].…”
Section: Resultsmentioning
confidence: 99%
“…When essential oils are used instead of single chemical compound, there have been challenges to examine their mechanism of action because of the large variances in the percentage each chemical compound present [7] depending on the extraction methods [8], the area of origin including differences in the geographic altitude of the areas [9], seasons the plants were harvested [10], and parts of the plants extracted [11,12]. It is thus important to utilize chemically-pure compounds or chemically-defined extracts as described in some recent studies [1317].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that major active substances (e.g., pinene, limonene, thymol, carvacrol) occurring in many EOs may exert strong anti-inflammatory, antioxidant, and antimicrobial effects, which are three crucial issues in chronic wound treatment [13][14][15][16][17]. Da Silva et al [18] demonstrated that essential oil extracted from Eugenia dysenterica DC leaves had the ability to induce fibroblast migration, possessed anti-inflammatory activity, and promoted angiogenesis in vivo, suggesting that its topical administration may result in faster regeneration of wounds. Mori et al [19] proved that lavender oil had immunomodulatory activity by upregulation of transforming growth factor-β (TGF-β).…”
Section: Administration Of Anti-inflammatory and Anti-oxidant Agentsmentioning
confidence: 99%